Esotropia Induced by a Chemotherapeutic Agent in a Patient with a Brain Tumor. - Bodack, Marie I. (Optometry & Visual Performance, 2014)
Patients who present with a sudden onset esotropia require a complete eye examination with dilation and cycloplegia to differentiate an accommodative from a non-accommodative cause. Non-comitancy, motility dysfunctions, and optic nerve anomalies must be ruled out. Cases of non-accommodative esotropia are often idiopathic but may be associated with neurologic problems. This paper will present a case report of a 6-year-old male who presented with a sudden onset esotropia. He had a prior history of surgical resection of an ependymoma and was currently under treatment with a chemotherapeutic agent. Treatment options for the esotropia are presented.